SANKSI ADMINISTRASI BAGI WAJIB PAJAK PAJAK PENGHASILAN ORANG PRIBADI DI KOTA PADANG - Arifka, Annisa (Kopertis Wilayah X, 2018)
Taxes as one of the state's sources of income, including in the field of state administration law, in this case is one of the tools that become a driving force in running the government must provide as much financial income to the State. The tax function is inseparable from tax purposes, while the tax objective is inseparable from the purpose of the country. Thus the tax objective must be aligned with the goals of the country which are the basis of the government's objectives. This research method is normative juridical, by obtaining the results that the implementation of administrative sanctions on personal income tax in the city of Padang are: administrative sanctions in the form of administrative fines of 36% (thirty six percent), administrative sanctions in the form of administrative interest of 57% (fifty-seven percent), as well as administrative sanctions in the form of administrative increases of 17% (seventeen percent). Factors causing personal income taxpayers to be subjected to administrative sanctions are due to delays caused by forgetting, because of the daily activities of taxpayers and because of frequent delays in payments, as well as a small portion who do not know about taxation and also a small part who know the time tax payment due date.